2002
DOI: 10.1128/mcb.22.10.3389-3403.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Activation of the MEK-Extracellular Signal-Regulated Kinase and MKK3/6-p38 Mitogen-Activated Protein Kinase Pathways Mediates Oncogenic ras-Induced Premature Senescence

Abstract: In primary mammalian cells, oncogenic ras induces premature senescence, depending on an active MEKextracellular signal-regulated kinase (ERK) mitogen-activated protein kinase (MAPK) pathway. It has been unclear how activation of the mitogenic MEK-ERK pathway by ras can confer growth inhibition. In this study, we have found that the stress-activated MAPK, p38, is also activated during the onset of ras-induced senescence in primary human fibroblasts. Constitutive activation of p38 by active MKK3 or MKK6 induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
312
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(345 citation statements)
references
References 60 publications
(97 reference statements)
31
312
0
Order By: Relevance
“…Mouse embryonic fibroblasts (MEFs) isolated from mkk7 mutant embryos display impaired JNK and Jun activation, reduced cell proliferation, premature senescence, as well as augmented susceptibility to stressinduced aging ( Figure 1 and Wada et al 6 ). In contrast, activation of p38-MAPK can also result in premature senescence of MEFs, 7 whereas pharmacological p38-MAPK inhibition induces increased cell proliferation, 8 To assess functional hierarchies and potential molecular crosstalks between the JNK and p38-MAPK stress pathways in cell fate decisions, we tested the effects of p38-MAPK modulation in mkk7 À/À MEFs. Surprisingly, inhibition of p38-MAPKa/b using the selective inhibitor SB202190 restored the proliferation of mkk7-deficient MEFs to that of MKK7-expressing control cells (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse embryonic fibroblasts (MEFs) isolated from mkk7 mutant embryos display impaired JNK and Jun activation, reduced cell proliferation, premature senescence, as well as augmented susceptibility to stressinduced aging ( Figure 1 and Wada et al 6 ). In contrast, activation of p38-MAPK can also result in premature senescence of MEFs, 7 whereas pharmacological p38-MAPK inhibition induces increased cell proliferation, 8 To assess functional hierarchies and potential molecular crosstalks between the JNK and p38-MAPK stress pathways in cell fate decisions, we tested the effects of p38-MAPK modulation in mkk7 À/À MEFs. Surprisingly, inhibition of p38-MAPKa/b using the selective inhibitor SB202190 restored the proliferation of mkk7-deficient MEFs to that of MKK7-expressing control cells (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it should also be considered that SB203580 has potential to stimulate Raf1 [23]. This kinase is involved in ERK activation and a model has shown that it may also be involved in MKK6 phosphorylation [24]. Therefore the relatively fast SB203580-induced phosphorylation of salmon MKK6b/c and ERK may also be due to a direct positive effect of the inhibitor on Raf-1 or other upstream signalling components.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of involvement of p53 in BU-induced senescence prompted us to hypothesize that activation of the Erk-p38 MAPK pathway may mediate the induction, because activation of the Erk-p38 MAPK pathway has also been implicated in the induction of cellular senescence [13,15,34,35]. Indeed, it was found that treatment of WI38 cells with BU activated Erk and p38 in a time-dependent manner and inhibition of Erk or p38 with a specific inhibitor significantly suppressed BU-induced WI38 cell senescence.…”
Section: Discussionmentioning
confidence: 99%